Core–Shell Nanoparticle Combined with Bacterial Targeting and Antibiotic Loading for Bacteria Tracing and Clearing. Issue 2 (23rd December 2022) - Hong, Qimin; Huo, Shicheng; Guo, Jingjing; Li, Bo; Sun, Yanping; Nie, Bin'en; Liang, Shanhui; Yang, Jianping; Yue, Bing
Abstract : Bacterial infections are a major complication in human healthcare. Bacteria tracing and targeted delivery of antibiotics to bacterial infection sites are being developed to reduce the high mortality caused by pathogenic bacterial infections. Owing to the challenges in accurate diagnosis of infection, particularly the identification of biomaterial‐related bacteria, the use of bacteria‐targeting nanomaterials has become increasingly important. Herein, magnetic core–shell mesoporous silica nanoparticles (MSNs) are fabricated for targeted drug delivery; the shell is modified with ubiquicidin (UBI)29‐41 for bacteria targeting, and vancomycin is loaded into the channels of the MSNs. The results demonstrate that magnetic core–shell MSNs display the desired functions of drug loading, bacteria targeting, detectability in magnetic resonance imaging, antibacterial action, and good in vitro biocompatibility. Magnetic core–shell MSNs have potential applications in the treatment of diseases caused by infections. Abstract : Magnetic core–shell mesoporous silica nanoparticles (MSNs) are fabricated for bacterial tracing and targeted drug delivery: the shell is modified with bacteria‐targeting peptides ubiquicidin(UBI)29‐41 to bind bacteria; the magnetic core (Fe3 O4 ) allows indirect detection of bacteria by visualizing nanoparticles under magnetic resonance; vancomycin is loaded into the MSN channels releasing at infection site to kill bacteria.